2003
DOI: 10.1260/147807703771799157
|View full text |Cite
|
Sign up to set email alerts
|

Tangible Design Media: Toward An Interactive CAD Platform

Abstract: This paper presents an interactive CAD platform that uses a tangible user interface to visualize and modify 3D geometry through manipulation of physical artifacts.The tangible user interface attempts to move away from the commonly used non-intuitive desktop CAD environment to a 3D CAD environment that more accurately mimics traditional desktop drawing and pin-up situations. An important goal is to reduce the apparent complexity of CAD user interfaces and reduce the cognitive load on designers. Opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The existing research on tangible interaction with CAD, such as [9][10] and the recent DeskCube by Autodesk Research [11] demonstrated tangible interfaces which are limited merely to perform navigation and modify viewpoints in CAD.The Luminous Planning table by MIT Media Lab and School of Architecture and Planning was developed for urban simulation [12].The integration between the physical building models and the digital drawing, plans and models allows real-time simulation of sun, wind, and shade being projected on the physical models located on the table.The building models can be moved or rotated to generate real-time feedback of the impact of the variations. However, the physical-digital integration is not feeding into parametric design software, and therefore the modification of the model is limited to changing the location and orientation of the buildings.To our knowledge, the use of tangible interaction, physical sensing, and Web2.0 as part of the tool and medium for parametric design has not been previously addressed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The existing research on tangible interaction with CAD, such as [9][10] and the recent DeskCube by Autodesk Research [11] demonstrated tangible interfaces which are limited merely to perform navigation and modify viewpoints in CAD.The Luminous Planning table by MIT Media Lab and School of Architecture and Planning was developed for urban simulation [12].The integration between the physical building models and the digital drawing, plans and models allows real-time simulation of sun, wind, and shade being projected on the physical models located on the table.The building models can be moved or rotated to generate real-time feedback of the impact of the variations. However, the physical-digital integration is not feeding into parametric design software, and therefore the modification of the model is limited to changing the location and orientation of the buildings.To our knowledge, the use of tangible interaction, physical sensing, and Web2.0 as part of the tool and medium for parametric design has not been previously addressed elsewhere.…”
Section: Introductionmentioning
confidence: 99%